Análisis de los factores que determinan la sostenibilidad y sustentabilidad de la economía social y solidaria para la industrialización y comercialización de la leche y sus derivados en los cantones los bancos, pedro Vicente Maldonado y Puerto Quito. - Duchi Chipantasi, Tania Cristina (2013)
A brief description about national milk production reveals that in Ecuador the biggest production of raw milk is located in the Sierra region. If we divided by region to the year 2011 was reported 76% comes from the Sierra, 17% from the Coast, 6% from the Amazon, and 1% from Galapagos Islands, the average production during the year 2012 was 6 375.323 liters per day by the entire country, this production comes from different farms, in different measure of Agricultural Production Units (APU's), the largest proportion of productive comes from APU's with less than 20 acres, which is equivalent to 2.8 million liters per day, the rest of the production 3 575.323 liters per day corresponds to medium and large farmer. Approximately 99.65% of the extracted raw milk is sold directly from the producer to small, medium and large producers who mostly have the capital and infrastructure required to produce variety of derived products under technical and improved ways